Diffuse-Type Tenosynovial Giant Cell Tumor of the Knee: Clinical Course After Anterior Open Synovectomy - Alessandro Bruschi; Eric Staals; Andrea Sambri; Luca Cevolani; Marco Gambarotti; Alberto Righi; Michele Fiore; Eleonora Villari; Stefano Pasini; Maria Giulia Pirini; Massimiliano De Paolis; Davide Maria Donati (Current Oncology, 2025)
Diffuse type tenosynovial giant cell tumor (D-TGCT) of the knee presents with stiffness, pain and swelling with surgery being the mainstay treatment. However, the literature lacks data on clinical course of range of motion, pain (ROM), and swelling after open synovectomy for D-TGCT. Therefore, this study aims to evaluate clinical course after open anterior synovectomy. A retrospective analysis was conducted on 214 patients treated for TGCT at our Institutions between 2010 and 2023. 51 patients with anterior knee D-TGCT who underwent open anterior synovectomy were included. Pre- and postoperative assessments included ROM, pain (VAS scale), and reported swelling. The mean knee flexion increased from 100° (SD 14.28) preoperatively to 131.8° (12.64) at 12 months post-surgery. Knee extension remained stable, ranging from 178.4° preoperatively to 179.2° at the final follow-up. Pain decreased from a mean of 5.0 (SD 2.8) preoperatively to 0.5 (SD 0.7) at 12 months. Swelling was initially reported in 90.4% of patients, with 95.74% of them showing improvement at six months, and 100% at 12 months. Open anterior synovectomy effectively improves knee function, pain, swelling in patients with anterior knee D-TGCT, although functional recovery may take up to 6–12 months.